Safety of Polyethylene Glycol Solution plus Ascorbic Acid for Bowel Preparation for Colonoscopy in Patients with Chronic Kidney Disease - Naoki Ohmiya; Yoshihito Nakagawa; Noriyuki Horiguchi; Takafumi Omori; Toshiaki Kamano; Kohei Funasaka; Mitsuo Nagasaka; Tomoyuki Shibata (Gastroenterology Research and Practice)
Introduction. Polyethylene glycol-electrolyte lavage solution plus ascorbic acid (PEG-ELS-Asc) has been recommended for colonoscopy, but little is known about the safety of PEG-ELS-Asc in patients with chronic kidney disease (CKD). The aim of this study was to determine its safety and efficacy in CKD patients. Methods. Blood and urine samples prospectively collected before and after same-day bowel preparation for colonoscopy with the conventional volume of PEG-ELS-Asc, vital signs before and after colonoscopy, and adverse events within 30 days postcolonoscopy were analyzed in consenting patients with CKD. The cleansing level was evaluated with the Boston bowel preparation score (BBPS) from colonoscopic findings. Results. Of 57 patients enrolled, 1 was excluded for refusal. Serum bicarbonate significantly dropped, and blood hemoglobin, serum total protein, albumin, aspartate aminotransferase, alanine aminotransferase, lactate dehydrogenase, total bilirubin, and uric acid significantly rose after bowel preparation, although these changes were not clinically important. Only in nondialysis patients did the platelet count and potassium significantly rise, although these changes were not clinically important either. Renal function, such as the urea, creatinine, and estimated glomerular filtration rate, was not significantly altered. An adequate bowel cleansing score, BBPS≥6, was achieved in 94% of patients. The blood pressure and heart rate were not significantly different between before and after colonoscopy in either nondialysis (n=32) or dialysis (n=19) patients. There were no adverse events associated with bowel preparation and colonoscopy within 30 days postcolonoscopy. Conclusions. The conventional volume of same-day bowel preparation with PEG-ELS-Asc may be safe and effective in CKD patients.